Negative concept of bound morphemes according to use theory (Raparin Journal of Humanities (RJH), 2023)
This research is about (Negative concept of bound morphemes according to use theory). It is an atttempt to determine those morphemes which carry the negative concepts. It  means they convey a weird and awkward meanings, that a speaker use them purposely to show the negative aspects of human nature. In spite of their negative meanings, in some circumstances they carry normal concepts. In this study, based on the available examples, depending on the data and figures, the precentage of both of them will be showed. This research will answer the following questions:What are those morpheme concepts which expresse the negative meanings? Which one of these concepts is more powerful and productive, and which one is the weakest? Are prefixes more productive, or suffixes? The purpose behind choosing this subject is to show the importantce of those morphemes and their negative meanings, compared to their normal use, which has an important scientific results.